Jewish travellers - Eisenstein, Judah David, 1854-1956.; Adler, Elkan Nathan, 1861-1946. (London : Routledge Curzon, 2005)
First published in 1930. The wandering Jew is a very real character in the great drama of history. He has travelled as nomad and settler, as fugitive and conqueror, as exile and colonist and as merchant and scholar. Of necessity bilingual and therefore the master of many languages, the Jew was the ideal commercial traveller and interpreter.Based on the volume of 24 Hebrew texts of Jewish travellers by J D Eisenstein, this volume begins with the ninth century. After the sixteenth century geographical discoveries had made the whole world familiar to most people. Consequently, the wandering J.
Introduction -- Eginhard of Franconia, A.D. 801 -- Ibn Khordadhbeh, c. 817 -- Eldad the Danite, c. A.D. 880 -- The epistle of R. Chisdai Ibn Shaprut to the king of the khozars and the king's reply, c. 960 -- Judah Halevi, 1085-1140 -- Benjamin of Tudela, 1165-73 -- Rabbi Petachia of Ratisbon, 1170-87 -- Rabbi Jacob Ben R. Nathaniel Ha Cohen. Twelfth century -- The Cairo Geniza. Thirteenth century -- Itinerary of Rabbi Samuel Ben Samson in 1210 -- Judah-al-Harizi, c. 1216 -- Rabbi Jacob, the messenger of Rabbi Jechiel of Paris, 1238-44 -- Isaac Ben Jospeh Ibn Chelo. The roads from Jerusalem, 1334 -- Elija of Ferrara, 1434 -- Rabbi Meshullam Ben R. Menahem of Volterra, 1481. I. II -- Obadiah da Bertinoro, 1487-90 -- David Reubeni, 1523-27 -- Jemsel the Karaite, 1641 -- David Azulai, 1755.
The texts and notes are in large part translated from J.D. Eisenstein's Ozar massaoth ("Treasure of travel"), a collection of 24 Hebrew texts. "[The present collection] begins with the ninth and ends in the middle of the eighteenth century ... The main object ... has been to give a conspectus of Jewish travel during the middle ages." cf. Pref.
Originally published in 1930.
Print version record.
eBooks on EBSCOhost
Keywords: Voyages and travels; Travel, Medieval; Palestine -- Description and travel; Voyages; Voyage -- Histoire -- 500-1500 (Moyen Âge); journeys; TRAVEL -- Museums, Tours, Points of Interest; TRAVEL -- Hikes & Walks; TRAVEL -- Budget; TRAVEL -- Special Interest -- Ecotourism; TRAVEL -- Parks & Campgrounds; TRAVEL -- Reference; TRAVEL -- Road Travel; TRAVEL -- Special Interest -- Adventure; Travel; Travel, Medieval; Voyages and travels; Middle East -- Palestine